2015
DOI: 10.1080/09297049.2015.1120860
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioral rating measures of executive function as predictors of academic outcomes in children

Abstract: Interrelations of two measurement methods (cognitive versus behavioral ratings) for executive function (EF) were examined and related to reading comprehension and math calculations in fourth and fifth grade students (n = 93) in the context of a diverse urban student population. Relations among measures within four EF processes (working memory, planning, inhibition and shifting) were modest; relations to academics were stronger. EF measures contributed to both academic outcomes even in the context of relevant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
108
4
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 65 publications
(119 reference statements)
17
108
4
9
Order By: Relevance
“…Our hypothesised univariate direct effect of WM on both math outcomes (composite versus specific math) was confirmed in this study, with effect sizes comparable with studies using performance‐based measures of WM in children with MBID (Henry & Winfield ; Brankaer et al ; Jansen et al ) and in typically developing primary school‐aged children (Friso‐Van Den Bos et al ; Gerst et al ). WM problems remained a significant risk factor in relation to both math outcome measures after taking IQ into account and with the composite CMT outcome when taking all EF problems into account.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Our hypothesised univariate direct effect of WM on both math outcomes (composite versus specific math) was confirmed in this study, with effect sizes comparable with studies using performance‐based measures of WM in children with MBID (Henry & Winfield ; Brankaer et al ; Jansen et al ) and in typically developing primary school‐aged children (Friso‐Van Den Bos et al ; Gerst et al ). WM problems remained a significant risk factor in relation to both math outcome measures after taking IQ into account and with the composite CMT outcome when taking all EF problems into account.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Finally, the academic tasks used in this study required foundational academic skills. It is possible that assessing higher-level skills, such as reading comprehension and math reasoning, would have revealed greater variability among the participants because of increased demands for higher-order cognitive skills, such as working memory and EF [10]. Nevertheless, associations were very strong with both the academic and adaptive outcomes, which suggests that interventions to enhance memory, both RM and PM, and EF are warranted.…”
Section: Discussionmentioning
confidence: 88%
“…In the general population, children with difficulties in aspects of executive function (EF), such as working memory, inhibitory control, and cognitive flexibility, are at increased risk for school failure [9,10], and those with EF difficulties in kindergarten are less likely to complete high school [11]. Thus, aspects of EF are considered core competencies for academic achievement [9].…”
Section: Introductionmentioning
confidence: 99%
“…Students often have to shift between different mental sets during learning and testing; therefore, a number of previous studies have examined the role of set‐shifting ability in predicting academic achievement. Several studies have reported a lack of an association between set‐shifting ability and academic performance (e.g., Cragg, Keeble, Richardson, Roome, & Gilmore, ; Espy et al, ; Lee, Ng, & Ng, ; Monette, Bigras, & Guay, ) whereas other studies have reported positive correlations between set‐shifting ability and academic performance (e.g., Bull, Espy, & Wiebe, ; Bull & Scerif, ; Cantin, Gnaedinger, Gallaway, Hesson‐McInnis, & Hund, ; Clark, Pritchard, & Woodward, ; Filippetti & Richaud, ; Gerst, Cirino, Fletcher, & Yoshida, ). Critically, two meta‐analyses have confirmed the positive association between set‐shifting ability and academic achievement.…”
Section: Set‐shifting Ability and Academic Achievementmentioning
confidence: 99%